3
(ii) cos2 A + cos2 (60° + A) + cos² (60° – A)
11
2​

Question

3
(ii) cos2 A + cos2 (60° + A) + cos² (60° – A)
11
2​

in progress 0
Ivy 3 months 2021-07-19T20:21:24+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-07-19T20:23:05+00:00

    Answer:

    above answer will help you

    0
    2021-07-19T20:23:14+00:00

    Step-by-step explanation:

    Answer:

    \huge\boxed{\bf \implies \frac{3}{2} }

    2

    3

    Step-by-step explanation:

    \begin{gathered} \bf \:{ cos}^{2}0°+{cos }^{2}60°+{cos}^{2}90° \\ \\ \bf \implies {1}^{2} + { \frac{1}{2} }^{2} + {0}^{2} \\ \\ \bf \implies \frac{2 + 1 + 0}{2} \\ \\ \boxed{\bf \implies \frac{3}{2} }\end{gathered}

    cos

    2

    0°+cos

    2

    60°+cos

    2

    90°

    ⟹1

    2

    +

    2

    1

    2

    +0

    2

    2

    2+1+0

    2

    3

Leave an answer

Browse

9:3-3+1x3-4:2 = ? ( )